2019
DOI: 10.1007/s10639-019-09941-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of blended learning for teaching and learning effectiveness in institutions of higher learning: An empirical investigation

Abstract: 3/19/2020 Exploring the role of blended learning for teaching and learning effectiveness in institutions of higher learning: An empirical investigation |…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 68 publications
3
105
0
7
Order By: Relevance
“…that provides more opportunities for reflection and feedback from students (Graham 2013;Moskal et al 2013;Dakduk et al 2018). BL is facilitated with virtual learning management systems such as Blackboard WebCT, Moodle, and other Web 2.0 platforms which are employed to facilitate collaborative learning between students and lecturers (Edward et al 2018;Anthony et al 2019). Accordingly, Aguti et al (2014) stated that 80 percent of institutions in developed regions dynamically employ BL approach to support teaching and learning, with 97 percent of institutions reported to be deploying one or more forms of IT mediated learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…that provides more opportunities for reflection and feedback from students (Graham 2013;Moskal et al 2013;Dakduk et al 2018). BL is facilitated with virtual learning management systems such as Blackboard WebCT, Moodle, and other Web 2.0 platforms which are employed to facilitate collaborative learning between students and lecturers (Edward et al 2018;Anthony et al 2019). Accordingly, Aguti et al (2014) stated that 80 percent of institutions in developed regions dynamically employ BL approach to support teaching and learning, with 97 percent of institutions reported to be deploying one or more forms of IT mediated learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BL is frequently used with terms such as integrated, flexible, mixed mode, multi-mode or hybrid learning (Garrison and Kanuka 2004;Moskal et al 2013). BL comprises integration of various initiatives, achieved by combining of 30% F2F interaction with 70% IT mediated learning (Anthony et al 2019). Similarly, Owston et al (2019) recommended that a successful BL delivery comprises of 80% high quality online learning integrated with 20% classroom teaching that is linked to online content.…”
Section: Introductionmentioning
confidence: 99%
“…Research into group work in blended courses at university has suggested a variety of reasons for the contextual success of group work. Some studies have attributed a key role to the teacher in linking the student in-class experience to that online (Anthony et al, 2019;Delialioglu & Yildirim, 2007;Díaz & Entonado, 2009). Others have focused on the way the teacher designs the content, communication and course activities (Kerres & De Witt, 2003), and the evaluation of designs for iterative improvement (Verkroost et al 2008).…”
Section: Research On Student Group Work At Universitymentioning
confidence: 99%
“…Jigsaw can be beneficially employed in conjunction with other teaching methods or alone, to suit the context, existing knowledge of learners and knowledge type (Anthony et al, 2019;Johnson & Barrett, 2017).…”
Section: Perceptions Of Knowledge and Approaches To Learningmentioning
confidence: 99%